دور وسائل الإعلام في تشكيل الوعي الاجتماعي لدى الشباب العماني دراسة تطبيقية على طلبة جامعة السلطان قابوس - Badar Ahmed Said Al Balushi
This quantitative study discusses the degree of social awareness of Sultan Qaboos University students, and the role of media influence in shaping that awareness. The problem is that media affect individuals and societies and influence the course of human development, and that there is a causal relationship between media exposure and human behavior. The influence of the media varies according to its functions, the social and cultural conditions. The study aimed to diagnose the impact of the media in forming social awareness and attitudes of Omani university youth, and its degree in promoting cultural awareness and social values. Discussing the forms of awareness presented by the media and its relationship to crystallizing the level of students’ knowledge and awareness of societal issues. Finally, monitoring the most important proposals to make media outputs better in forming positive social awareness in the Sultanate. The researcher used the social survey method. The study population consisted of all students of Sultan Qaboos University in the four stages, and their number was (15840) students. A stratified random sample of (2272) male and female students was selected according to Jersey and Morgan's table. The researcher used the quantitative approach to collect data using a questionnaire consisting of (192) statements distributed on (4) aspects. The study findings revealed that: Social media came first in shaping the degree of social consciousness, followed by websites at a high rate, and government television channels at a lower rate. Social media has been the most influential on many issues, followed by the Internet and private and government media channels, respectively. The Internet was the most effective means of affirming freedom and democracy and promoting equal values of social participation. Social media is the most influential in issues of marriage and divorce, and the problems of youth and adolescents. Internet sites were the most influential on issues of religious and political violence, financial corruption, and witchcraft. Meanwhile, the state media has emphasized the issues of drug addiction, health, and employment. The preferred media items were political programs, sports and entertainment, films, series and plays. The study recommended developing national audio-visual programs, increasing media programs interested in social issues, and establishing media observatories to follow up and monitor information and rumors published on social media about social, political and cultural issues in the Sultanate of Oman.